Accelerating Electron‐Transfer Dynamics by TiO2‐Immobilized Reversible Single‐Atom Copper for Enhanced Artificial Photosynthesis of Urea - Li, Dong; Zhao, Yunxuan; Miao, Yingxuan; Zhou, Chao; Zhang, Li‐Ping; Wu, Li‐Zhu; Zhang, Tierui (Advanced materials (Weinheim), 2022)
Photocatalysis as a sustainable technology is expected to provide a novel sight for the green synthesis of urea directly using N2, CO2, and H2O under mild conditions. However, the fundamental issue of inefficient electron transfer in photocatalysis strongly hinders its feasibility, especially for the above multi‐electron‐demanding urea synthesis. Herein, an effective strategy of accelerating electron‐transfer dynamics is reported by TiO2‐immobilized reversible single‐atom copper (denoted as Cu SA‐TiO2) to enhance the performance for photosynthesis of urea from N2, CO2, and H2O. As revealed by a series of quasi‐in‐situ characterizations (e.g., electron paramagnetic resonance, and wavelength‐resolved and femtosecond time‐resolved spectroscopies), the expedited dynamics behaviors originating from reversible single‐atom copper in as‐designed Cu SA‐TiO2 (electron extraction rate: over 30 times faster than the reference photocatalysts) allow the assurance of abundant and continual photogenerated electrons for multi‐electron‐demanding co‐photoactivation of N2 and CO2, resulting in considerable rates of urea production. The strategy above for improving the photoelectron‐extraction ability of photocatalysts will offer a high‐efficiency and promising route for artificial urea photosynthesis and other multi‐electron‐demanding photocatalytic reactions. Accelerating electron‐transfer dynamics by TiO2‐immobilized reversible single‐atom copper is proposed for enhancing artificial urea photosynthesis using N2 and CO2 in pure H2O. The quasi‐in‐situ characterizations reveal that the accelerated electron‐transfer dynamics can be attributed to the reversibility of single‐atom Cu for ensuring multi‐electron‐demand and supply of urea photosynthesis, thereby yielding as high as 432.12 µg gcat.−1 of urea.